Comparison on the Content of Policing and Public Administration - Balla, Zoltán (Magyar Rendészet, 2014)
Policing is a part of public administration. Both are influenced by the political and economic characteristics of the society. The general task of public administration is the realization of public interest and the carrying out of different public duties. Policing ensures public safety by exercising public authority through legitimate means. Policing is carried out mainly by administrative bodies and to a lesser extent by local governmental and non-governmental bodies, but a policing model has appeared in the organization of the legislative power.